Pengaruh Komunikasi Krisis Oleh Brand Pinkflash Terhadap Reputasi Merek Di Kalangan Mahasiswa Jakarta - Sarah Diva Azzahra; Aisyah Zahwa Adisty; Qiana Monica; Sadiyah El Adawiyah (CV. ITTC INDONESIA, 2026)
The development of social media has made brand crises, particularly in the cosmetics industry, increasingly widespread and difficult to control. This study aims to analyze the influence of crisis communication conducted by the Pinkflash cosmetics brand on brand reputation among female students in Jakarta. The research focused on the issue of Pinkflash product recall by the Indonesian Food and Drug Authority (BPOM RI), which was announced on November 30, 2024, and which was again widely discussed on social media in 2025. This study used a quantitative approach with a survey method and referred to Social-Mediated Crisis Communication (SMCC) Theory. Data were obtained from 32 female students aged 18–25 in Jakarta using a Likert-scale questionnaire. The results showed that crisis communication delivered clearly, transparently, and accompanied by corrective measures can help maintain brand reputation amidst a re-emerging crisis. These findings confirm that an appropriate crisis communication strategy plays a crucial role in maintaining public trust in the digital era.